Mi̇lli̇ kayaklı koşucularda AGT (anji̇yotensi̇nojen) M235T VE HIF1A (hi̇poksi̇yle indüklenenfaktör-1 ALFA) C111A poli̇morfi̇zm dağılımlarının incelenmesi̇ - ULUCAN, KORKUT (My University, 2018)
MATERYAL-METOT: Çalışmamıza 34 Milli Kayakçı katılmıştır. Onam formları imzalatılarak toplanan kan örneklerinden DNA izolasyonu; Invitrogen (Van AllenWayCarlsbad,CA, USA) ticari kiti kullanılarak tamamlanmıştır. PPAR ve IL-6 genotiplemeleri için gerçek zamanı polimeraz zincir reaksiyonu (qPCR) protokolü ile gerçekleştirilmiştir. BULGULAR: PPARA analizinde 34 kayakçıdan 23’ünün (%67,6) GG, 8’inin (%23,5) GC ve 3’ünün (%8,9) CC genotipinde olduğu belirlenmiştir. Allel dağılımları incelendiğinde G Allelinin %79,4 oranında, C Allelinin ise %20,6 oranında olduğu gözlemlenmiştir. IL-6 genine bakıldığında ise 17 Kayakçının (%50) GG ve 17’sinin (%50) GC genotipinde olduğu saptanmıştır. IL-6 için CC genotipindeki kayakçıya rastlanmamıştır. Allel dağılımları; %75 G, %25 C şeklindedir. TARTIŞMA: Çalışma kohortumuzda PPARA rs4253778 polimorfizminde GG genotipi ve G allelinin baskın olduğu, IL-6 rs1800795 polimorfizminde ise GG ve GC genotiplerinin eşit sayıda olup G Allelinin baskın olduğu saptanmıştır. PPARA ve IL- 6 genlerindeki bu polimorfizmlerin sporcu olmayı hedefleyen bireyler için spor branşlarının belirlenmesinde ve branş içi yönlendirmelerde etkin olduğunu düşünmekteyiz.

INTRODUCTION: Athletic performance is a common combination of hereditary genetic abilities and subsequent environmental factors. Current research on athletic performance focuses on genetic variants that make a significant contribution to people's performance. Individual characteristics such as endurance, strength, power, muscle coordination and motivation are reported to have genetic background. Sports genetics studies involve a comprehensive investigation of the identification of genes that affect athletic performance, clarity of movement mechanisms and determination of their susceptibility to athletic performance. In this study, we aimed to determine the distribution of IL-6 (rs1800795) and PPARA (rs4253778) polymorphisms, which are known to affect the athletic performance, among the National Skiers. MATERIALS-METHODS: 34 skiers participated in the study. After signing of consent forms, DNA isolation from collected blood samples was performed with Invitrogen (Van AllenWay, Carlsbad, CA, USA) commercial kit. Real-time polymerase chain reaction (qPCR) protocol for PPARA and IL-6 genotyping was performed. RESULTS: In PPARA analysis, it was determined that 23 (67.6%) of the 34 skiers had GC genotype, 8 (23.5%) had GC and 3 (8.9%) had CC genotype. When allele distributions were examined, it was observed that G allele had the ratio of 79.4% and C had 20.6%.When the IL-6 was examined, 17 (50%) skiers were found to be GG genotype and 17 (50%) were found to be GC genotypes. For the IL-6, the skier in the CC genotype was not found. Allele
Distribution of peroxisome proliferator-activated receptors alpha (PPARA) RS4253778 and interleukin-6 (IL-6) RS1800795 polymorphisms in national running skiers